Lionboy - Corder, Zizou; Van Deelen, Fred (New York Puffin, 2003)
In the near future, a boy with the ability to speak the language of cats sets out from London to seek his kidnapped parents and finds himself on a Paris-bound circus ship learning to train lions
Keywords: Cats -- Fiction; Circus -- Fiction; Human-animal communication -- Fiction; Kidnapping -- Fiction; Lion -- Fiction; Voyages and travels -- Fiction